THE ROLE OF THE OLDER GENERATION IN THE DEVELOPMENT OF CIVIL SOCIETY AND MORAL DEVELOPMENT OF YOUTH - Akhmadiev N. M. (Academia Science Repository, 2023)
This article explores the role and importance of the older generation in the development of civil society and the moral education of young people, the analysis of the important tasks facing older people in the process of educating the thinking of the younger generation. generation described.